Profile of pediatric ocular trauma in mid western hilly region of Nepal - Dulal, S; Ale, JB; Sapkota, YD (Nepalese Journal of Ophthalmology, 2012)
Introduction: Majority of blinding ocular injuries can be prevented. Objective: To describe the epidemiology of ocular trauma in children. Material and methods: A retrospective review of medical records of the patients aged below 16 years who attended the Himalaya Eye Hospital, Pokhara with history of ocular injury. Results: Of 6,829 pediatric patients, 554 (8.1 %) had ocular trauma. The ocular trauma was more prevalent (38.1 %) in the age group of 5 – 10 years followed by 10-15 years (16.6 %). The boys (62 % vs 38 %) were more prone to ocular trauma than girls (RR = 1.7 and 95 % CI = 1.41 - 2.02). Of 554 ocular injuries, 32 (5.8 %) were open globe injuries. Sub-conjunctival hemorrhage was the commonest presenting finding in 96 (17.3 %) subjects. Forty-seven (8.5 %) of them attended the hospital after 15 days of injury. Home was the most common place for trauma (n =204, 36.8%), followed by playground (n = 140, 25.3 %). Conclusion: Children between the ages of 5-10 years are most vulnerable to ocular trauma. Home is the commonest place for ocular injury followed by playground. By adopting some common safety factors or by reducing the ocular injury risks factor, ocular trauma can be greatly reduced. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5865 NEPJOPH 2012; 4(1): 134-137